2019
DOI: 10.5455/aim.2019.27.8-11
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Interaction of the Active Compounds of Scurrula Atropurpurea with the RANK/RANKL/OPG System in Diabetoporosis

Abstract: Introduction: Diabetoporosis is a very complex health problem in Indonesia. One approach to the problem is through native Indonesian herbal medicine. The application of Scurrula atropurpurea in the treatment of diabetoporosis has not been revealed, so preliminary in silico study needs to be done. Aim: The purpose of the present study was to analyze the interaction between the active compound of Scurrula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
0
1
Order By: Relevance
“…On the other hand, the research in silico interaction of rutin with the RANK/RANKL system in diabetoporosis showed that the initial interaction of RANK with rutin will facilitate the bond of RANK to RANKL. This is in contrast to previous findings that rutin decreases the activity of RANKL [ 99 ].…”
Section: Mechanism Studiescontrasting
confidence: 99%
“…On the other hand, the research in silico interaction of rutin with the RANK/RANKL system in diabetoporosis showed that the initial interaction of RANK with rutin will facilitate the bond of RANK to RANKL. This is in contrast to previous findings that rutin decreases the activity of RANKL [ 99 ].…”
Section: Mechanism Studiescontrasting
confidence: 99%